E-learning and problem based learning integration in cardiology education. - Gürpinar E; Zayim N; Basarici I; Gündüz F; Asar M; Oguz N (Anatolian Journal of Cardiology / Anadolu Kardiyoloji Dergisi, 2009)
OBJECTIVE: The aim of this study was to determine students' satisfaction with an e-learning environment which is developed to support classical problem-based learning (PBL) in medical education and its effect on academic achievement. METHODS: In this cross-sectional study, students were provided with a web-based learning environment including learning materials related to objectives of the subject of PBL module, which could be used during independent study period. The study group comprised of all of the second year students (164 students) of Akdeniz University, Medical Faculty, during 2007-2008 education period. In order to gather data about students' satisfaction with learning environment, a questionnaire was administered to the students. Comparison of students' academic achievement was based on their performance score in PBL exam. Statistical analyses were performed using unpaired t test and Mann Whitney U test. RESULTS: Findings indicated that 72.6% of the students used e-learning practice. There is no statistically significant difference between mean PBL performance scores of users and non-users of e-learning practice (103.58 vs. 100.88) (t=-0.998, p=0.320). It is found that frequent users of e-learning application had statistically significant higher scores than non-frequent users (106.28 vs. 100.59) (t=-2.373, p=0.01). In addition, 72.6% of the students declared they were satisfied with the application. CONCLUSION: Our study demonstrated that the most of the students use e-learning application and are satisfied with it. In addition, it is observed that e-learning application positively affects the academic achievement of the students. This study gains special importance by providing contribution to limited literature in the area of instructional technology in PBL and Cardiology teaching.